Representing Bodies and Identities in Global Exhibitions - Cavazzuti, Federica (Annali di Ca’ Foscari: Serie Orientale, 2023)
The paper focuses on Japanese female photographers in international art exhibitions. Until recently, Japan’s photographic field was predominantly male‑dominated. Traditionally, women were considered incompetent with technical equipment and this long-enduring stereotype limited them to passive roles as models. However, from the late 1980s/early 1990s, a shift occurred, with female photographers gaining prominence. In parallel, the representation of Japanese women artists in international venues started to rise and more names began circulating in the global art circuits. This essay inspects in particular one of the most important events on the scene: the Art Biennale in Venice, the oldest and most prestigious of these large-scale exhibitions. Two important shows, held respectively in 2005 and 2009 at the Japan pavilion of the Venice Biennale, provide the starting point for this analysis: they were the only exhibitions ever dedicated to women photographers by the pavilion in its 70‑year‑old history. The artworks of Ishiuchi Miyako and Yanagi Miwa were showcased, two of the most important women photographers in recent years.